Advancements of nanotechnological strategies as conventional approach for heavy metal removal from industrial wastewater: Start-of-the-art review - Sakshi Raturi; Swati Kumari; Kovács András; Rohit Khargotra; Viktor Sebestyén; Tej Singh (Current Research in Green and Sustainable Chemistry)
Multi-faceted growth and progression of the healthy and economical society, depends upon access to clean and safe water. Rapidly over-growing population, increased in industrialization, urbanisation, and widespread practices in agricultural have all together been contributing to the production of more rapid wastewater discharge, which has not only polluted or contaminated the water but also have played a role in killing the aquatic life. One class of harmful water pollutants that is frequently found in the environment is heavy metals. Almost every transition metal has the ability to dissolve as ions in water. Heavy metals including Pb, Cd, Hg, As, Se and others can contaminate water supplies. Conventional methods for waste-water treatment have peculiar challenges including economic feasibility, energy consumption, environmental hazards, time spent, etc. To overcome these limitations, nanotechnology have been developed, which has its greater extent of application in water treatment area. Nanoparticles have a greater probability of removing heavy metals from wastewater treatment due to their effective surface characteristics and chemical activity. This review focuses on the numerous treatment procedures that have been developed recently and also been applied practically for eradication of heavy metals from waste-water of various industries.